THE STUDIES OF THE BILDUNGSROMAN HERMAN HESSE'S DEMIAN IN AND CHARLES DICKENS' DAVID COPPERFIELD - M Supriyatno (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2011)
Supriyatno Unisda Lamongan diglossiafbs@gmail.com Abstrak Bildungsroman play an important role in the literary movement. Its role is centered on the development of the central character or education. Bildungsroman novels aimed at guiding the reader to greater personal enrichment on an adventure of the protagonist from youth to adulthood. Charles Dickens is known as one of the writers who focus on the development of the central character or education. One of his best works are David Copperfield. David Copperfield David Copperfield describes life as the main character in the story, from childhood to adulthood. Another writer Herman Hesse's attention to the way the character of emotional maturity. Demian is a work that describes the search Demian Hesse, the main character, to the emotional maturity of his life. Therefore, this study will be studied by using the characteristics of the Bildungsroman in David Copperfield and Demian. key words: bildungsroman, protagonist, personality development   Abstrak Bildungsroman berperan penting dalam gerakan sastra. Peranannya berpusat pada pengembangan atau pendidikan karakter sentral. Novel Bildungsroman bertujuan membimbing pembaca untuk pengayaan pribadi yang lebih besar pada petualangan protagonis dari masa muda hingga dewasa. Charles Dickens dikenal sebagai salah satu penulis yang perhatian pada pengembangan atau pendidikan karakter sentral. Salah satu karya terbaiknya adalah David Copperfield. David Copperfield menggambarkan tentang kehidupan David Copperfield sebagai karakter utama dalam cerita, dari masa kanak-kanak sampai dewasa. Herman Hesse penulis lain yang perhatian pada perjalanan kematangan emosi karakter. Demian adalah karya Hesse yang menggambarkan pencarian Demian, karakter utama, untuk kematangan emosional dalam hidupnya. Oleh karena itu, penelitian ini akan dipelajari dengan menggunakan karakteristik Bildungsroman pada novel David Copperfield dan Demian. kata Kunci: Bildungsroman, protagonist,  personality development